COMMUNITY STRUCTURE AND DIVERSITY OF MACROZOOBENTHOS IN QUARRY RIBNICA’S CREEK AS INDICATOR OF SURFACE WATER MANAGEMENT - Semir Dorić; Adnan Čučuković (Genetics & Applications, 2017)
Benthic macroinvertebrata (macrozoobenthos) are widely used for water quality assessments because they are considered as one of the best indicators of habitat quality in running waters, very conventionally called as „river health“. Benefits of research on macroinvertebrates include the quick assessment of biological resources for conservation purposes and the detection of water pollution. This research was performed in accordance with the EU Water Framework Directive (WFD). AQEM methodology was used for macrozoobenthos specimen collection from six sampling sites along quarry Ribnica’s main hydroecosystems – the Forest creek (quarry's water supply system) and the estuary of the river Ribnica (Mar-Sep, 2016). Laboratory analyses were carried out for the purpose of separation, counting and final taxonomic identification of organisms. Cluster analysis and diversity index computing were performed using BioDiversity Pro 2.0 software. Our findings suggest the existence of 15 taxa from classes Gastropoda, Hirudinea and Insecta with a total number of 454 sampled individuals. The Insecta class was the most numerous one with respect to the species found, including larvae of the orders Ephemeroptera, Plecoptera, Trichoptera and Diptera. Shannon-Weaver and Simpson diversity indices revealed highly developed communities of aquatic macroinvertebrates at all sampling sites. Water quality along quarry Ribnica based on macrozoobenthos indicator species of saprobity was found to be classified into moderate, low and non to very low polluted (Quality class I-II). Further long-term monitoring studies of macrozoobenthos are necessary in order to keep track of the good ecological status (GES) observed at quarry Ribnica’s aquatic ecosystems.